2016
DOI: 10.1016/j.ijdevneu.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐parkinsonian effects of fluvoxamine maleate in maternally separated rats

Abstract: Exposure to early life stress has been shown to result in anxiety-like symptoms and exacerbates degeneration of dopaminergic neurons in a rat model of Parkinson's disease (PD). First line treatment for anxiety disorders includes the use of Fluvoxamine maleate (FM). In this study, we investigated whether treating anxiety-like symptoms with FM has an effect in alleviating the neurotoxic effects of 6-OHDA in a parkinsonian rat model. Early maternal separation was used to create a rat model that depicts anxiety-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…This study is aimed at assessing the long-term effects of Fluvoxamine in managing anxiety/depressive-like symptoms and cognitive deficits and reducing motor dysfunctions in a parkinsonian rat model. Our objective was to evaluate the Plasma corticosterone levels were measured to confirm the effectiveness of the stress protocol in dysregulating the HPA axis resulting in anxiety/depressive symptoms and cognitive deficits [27,30,36,37,56]. We found that maternally separated (MS) rats had higher corticosterone levels when compared to nonseparated (NS) rats in agreement with a study by Daniels et al [27] who showed that stress elevates blood corticosterone levels.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This study is aimed at assessing the long-term effects of Fluvoxamine in managing anxiety/depressive-like symptoms and cognitive deficits and reducing motor dysfunctions in a parkinsonian rat model. Our objective was to evaluate the Plasma corticosterone levels were measured to confirm the effectiveness of the stress protocol in dysregulating the HPA axis resulting in anxiety/depressive symptoms and cognitive deficits [27,30,36,37,56]. We found that maternally separated (MS) rats had higher corticosterone levels when compared to nonseparated (NS) rats in agreement with a study by Daniels et al [27] who showed that stress elevates blood corticosterone levels.…”
Section: Discussionsupporting
confidence: 79%
“…A total of 40 male Sprague-Dawley (SD) rats, weighing between 6 g at postnatal day (PND) 1 and 300 g at PND 76, was used. Pregnant SD rats were obtained from the Biomedical Resource Unit of the University of KwaZulu-Natal and were housed in polypropylene cages (38 × 32 × 16 cm) under controlled temperature (21 ± 2°C) and humidity (55-60%) until they gave birth [30]. At birth, pups were crossfostered and randomly divided into 4 groups as follows: (1) nonmaternally separated (NS), (2) nonmaternally separated treated with Fluvoxamine (NSF), (3) maternally separated (MS), and (4) maternally separated treated with Fluvoxamine (MSF) (n = 10/group).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The publications included in the analysis were:(Adrover et al 2007; Alonso, Navarro, and Rodriguez 1994; Baharnoori, Bhardwaj, and Srivastava 2013; Baier et al 2014; Bakos et al 2004; Basta-Kaim et al 2011; Berger et al 2002; Bingham et al 2013; Bitanihirwe et al 2010; Brenhouse, Lukkes, and Andersen 2013; Cabib, Puglisi-Allegra, and D’Amato 1993; Cai et al 2013; Camp, Robinson, and Becker 1984; Carboni et al 2010; Chocyk et al 2011; Kwok Ho Christopher, Choy, De Visser, and Van Den Buuse 2009; K. H C Choy and van den Buuse 2008; Cory-Slechta et al 2009; Cory-slechta et al 2013; Dallé, Daniels, and Mabandla 2016; Delattre et al 2016; L. W. Fan et al 2011; L.-W.…”
Section: Resultsmentioning
confidence: 99%
“…Electro-convulsive therapy, Psychotherapies and Cognitive behavior therapy are particularly effective for the most severe and resistant depressions 1 . Fluvoxamine is one of the antidepressants commonly used as first line treatment for major depressive disorders 2,3 SSRIs (selective serotonin reuptake inhibitor) are antidepressant drugs that increase serotoninergic neurotransmission via the selective inhibition of neuronal reuptake of serotonin 4,5 . Fluvoxamine is BCS class II drug which having low solubility and high permeability but it is practically soluble in ethanol, so it is suitable for formulating nanosuspension.…”
Section: Introductionmentioning
confidence: 99%